Physiological responses of Amaranthus cruentus L. to drought stress under sufficient- and deficient-nitrogen conditions - Cechin, Inês [UNESP]; da Silva, Laura Prado [UNESP]; Ferreira, Elisa Teófilo [UNESP]; Barrochelo, Sarah Corrêa [UNESP]; de Melo, Fernanda Pereira de Souza Rosa [UNESP]; Dokkedal, Anne Ligia [UNESP]; Saldanha, Luiz Leonardo [UNESP] (Public Library of Science (PLoS), 2022)
Water and nitrogen availability are two major environmental factors that can impair plant growth, and when combined, their effects on plant performance can be either intensified or reduced. The objective of this study was to analyze the influence of nitrogen availability on the responses of Amaranthus cruentus’s metabolism to water stress. The plants were cultivated in plastic pots filled with vermiculite, kept under greenhouse conditions, and were watered three times a week with 70% of a full strength nitrogen-free Long Ashton solution, containing 1.97 or 9.88 kg N ha−1 as ammonium nitrate. Photosynthetic parameters were evaluated in planta, and leaves were harvested for chemical analysis of photosynthetic pigments, proline, and phenolic contents. Higher nitrogen supply increased the shoot dry matter, photosynthetic pigments, photosynthesis, stomatal conductance, transpiration, total leaf nitrogen, proline, nitrate, and ammonium but reduced the concentration of flavonoids and total phenols. Six days of water stress did not affect dry matter, photosynthetic pigments, leaf nitrogen, ammonium, or specialized metabolites but increased the proline under high nitrogen and negatively affected stomatal conductance, transpiration, photosynthesis, relative water content, instantaneous water use efficiency, and leaf nitrate. The negative effect was more pronounced under high nitrogen supply. The results show that the addition of a high amount of nitrogen made the physiological processes of plants more sensitive to water stress, indicating that the plant response to water restriction depends on the interaction between the different environmental stressors to which the plants are subjected.